Students' Perceptions of a Canva-Based Web Learning Platform for Real Analysis: A Descriptive Quantitative Study - Hakim, Rahman Nul; Fajriah, Noor; Suryaningsih, Yuni (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
Real Analysis is often recognized as one of the most difficult subjects in undergraduate mathematics because of its abstract ideas and the requirement for precise proof methods. Despite its importance, the scarcity of interactive learning resources and the low English proficiency of students have impeded effective understanding. This research aims to investigate students' perceptions of Canva as a web-based learning platform to address these challenges in teaching Real Analysis. A descriptive quantitative approach was utilized, involving 34 students from the Mathematics Education program at Universitas Lambung Mangkurat, chosen through purposive sampling. Data were gathered using a Likert-scale questionnaire assessing three dimensions: content quality, speed and performance, and usability. The findings indicated that students responded overwhelmingly positively, with all metrics achieving scores in the "excellent" range, including content clarity, navigation ease, and platform responsiveness. These results suggest that Canva is a user-friendly platform that positively supports students' engagement and perceived understanding of abstract mathematical concepts. The implications of this study underscore Canva's potential as an accessible and innovative educational resource for improving digital learning experiences in advanced mathematics, motivating educators to integrate visually-oriented platforms into the creation of interactive and inclusive learning settings.